Phase Transition, Dielectric and Piezoelectric Properties of Lead-Free Piezoelectric (K1/2Na1/2)NbO3 – Bi(Zn2/3Nb1/3)O3 Ceramics. Issue 1 (2nd January 2016) - Sutapun, Manoon; Muanghlua, Rangson; Vittayakorn, Naratip
Abstract : The lead–free piezoelectric ceramics on the binary system of (1- x )(K1/2 Na1/2 )NbO3 – x Bi(Zn2/3 Nb1/3 )O3 [(1- x )KNN– x BZnN]; x = 0.01–0.10 were fabricated by the solid state reaction method. The structure and phase transition were determined by X-ray diffraction.The results of XRD patterns suggested that Bi(Zn2/3 Nb1/3 )O3 completely diffuse into the (K1/2 Na1/2 )NbO3 lattices to form a solid solution. The crystal structure was in an orthorhombic phase for x ≤ 0.01. When reaching 0.01 < x ≤ 0.07, crystal structure became a rhombohedral phase and transformed to a pseudo-cubic structure for x > 0.07. The dielectric data shows that the amount of Bi(Zn2/3 Nb1/3 )O3 added in the (K1/2 Na1/2 )NbO3 decreases the ferroelectric – paraelectric transition temperature progressively. Furthermore, optimum piezoelectric and ferroelectric properties were observed at the composition, x = 0.01: effective piezoelectric coefficients ( d33 *) = 498 pm/V, remanent polarization ( Pr ) = 23.3 µC/cm 2, coercive field ( Ec ) = 14 kV/cm, maximum strain ( Smax ) = 0.3% and Curie temperature ( TC ) = 380°C. The results of this study show that KNN with a small amount of Bi(Zn2/3 Nb1/3 )O3 ( x = 0.01) can be one of lead-free piezoelectric ceramic candidate.